Napoletan Sculpture of the 1340s between Tino di Camaino and Andrea Pisano: The Work of Pacio e Giovanni Bertini - Lopukhova, Marina A. (Actual Problems of Theory and History of Art, 2019)
Since Tino di Camaino, a Sienese carver and architect, came to the Anjou Court the developmentof the art of sculpture in the Medieval and Renaissance Naples would be always, while chronologically and style-wise discrete, marked by strong Tuscan presence. In the 1320–1330s, Tino’s remarkable style became the style-forming for the Gothic Napoletan sculpture, primarily memorial, which to a certain extent, interpreted the art of his teacher Giovanni Pisano. However, it was not the only style line existing in the Napoletan sculpture in the mid-Trecento. The art of Pacio and Giovanni Bertini gives an example of combination of some traits of Tino’s manner and more classical aspirations inspired by the Roman Proto-Renaissance sculpture (such as Arnolfo di Cambio) and the Florentine sculpture of the 1330s (Andrea Pisano). Descendants from Andrea Pisano’s workshop and mentioned in Napoletan documents as marmorarii fratres and unknown in Florence, they created the most prominent sculptural complex of the 14th-century Naples in both programmatic and artistic relevance. This is the grand tomb of the King Robert Anjou in the Franciscan convent of Santa Chiara (started in 1343). Besides, a number of fragments in different memorial complexes of the same monastery Santa Chiara, in the church Sant’Andrea alla Zecca, and in Certosa di San Martino are attributed to the brothers. The critics of the mid-20th century tried to show the creative individuality of each one. In some cases they evidently completed the projects started by Tino di Camaino, finding themselves in the predetermined style context as in the case with the monumental king’s tomb. The most interesting example of the independent style of the two brothers, where the Florentine language and, first of all, the décor of the Florentine campanile’s lower circle made by Andrea Pisano, appeared more prominently, are the reliefs depicting the history of Saint Catherine of Alexandria, which probably used to decorate the screen of the Santa Chiara church and was severely damaged during the bombing in 1943 (now stored in the monastery museum). They reveal a very compact compositional approach, a very characteristic figure and face type, a strong interest to the landscape, architectural and interior details as to the citations from the Antiquity. A comparative analysis of these compositions with the campanile’s decoration raises the issue of participation of Pacio or at least the younger brother Giovanni in making the Florentine reliefs within the Pisano workshop.